Global, regional, and national burden of cataract among older adults from 1990 to 2021: a comprehensive analysis based on the global burden of disease study 2021 - Wan, Zhongqi; Bai, Jianhao; Wang, Weifang; Peng, Qing (Frontiers in Medicine, 2025)
ObjectiveTo assess the global, regional, and national burden of cataract among individuals aged 60 years and older from 1990 to 2021, and to examine disparities by age, sex, socio-demographic level, and geographic region using data from the Global Burden of Disease Study (GBD) 2021.MethodsWe extracted cataract prevalence data for 204 countries from GBD 2021 and analyzed age-standardized prevalence rates (ASPRs) across regions and Socio-demographic Index (SDI) levels. Sex- and age-specific patterns were assessed. Age-period-cohort modeling, decomposition analysis, absolute and relative inequality metrics, and frontier analysis were applied to assess temporal trends, demographic drivers, and disparities.ResultsIn 2021, the global ASPR of cataract among the elderly was 7,748.5 per 100,000, with significantly higher rates in South Asia. Females had consistently higher ASPRs than males across all age groups and regions. Prevalence increased with age, peaking in those aged ≥95 years. Age-period-cohort (APC) analysis revealed that aging is the dominant driver of burden, with minor period and cohort effects. Decomposition showed that global prevalence increases were largely driven by population growth (87.4%), with smaller contributions from aging and epidemiological change. Substantial inequality persisted: low-SDI countries bore disproportionately higher burdens, with minimal improvement from 1990 to 2021. Frontier analysis revealed large performance gaps even among similarly developed countries.ConclusionCataract remains a major and unequal public health burden among older adults, particularly in low- and middle-SDI settings. Addressing service delivery inefficiencies, expanding surgical coverage, and implementing equitable aging-focused eye care policies are essential to reduce avoidable visual impairment globally.